2009
DOI: 10.1007/s00415-009-5419-5
|View full text |Cite|
|
Sign up to set email alerts
|

Rural environment and risk factors of amyotrophic lateral sclerosis: a case–control study

Abstract: The aetiology of sporadic ALS is still unknown. Links with several environmental factors have been suggested, and some epidemiological studies have shown an increased incidence of ALS in rural populations. This study was designed to investigate risk exposures in a well-delimited rural population and to assess whether rural residency or occupations, such as farming, were associated with an increased risk of developing ALS. A prospective case-control-study of 108 sporadic ALS cases matched by age and sex to 122 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In a study performed with 108 sporadic ALS patients, it was found that contact with agricultural chemicals or with animals associated with agriculture played a potential role in the disease [19]. Additionally, working in the agricultural field or living in urban regions have been indicated as potential risk factors for the development of ALS [19,20]. study.…”
Section: Discussionmentioning
confidence: 98%
“…In a study performed with 108 sporadic ALS patients, it was found that contact with agricultural chemicals or with animals associated with agriculture played a potential role in the disease [19]. Additionally, working in the agricultural field or living in urban regions have been indicated as potential risk factors for the development of ALS [19,20]. study.…”
Section: Discussionmentioning
confidence: 98%
“…Rural environment was proposed, in some series 16,17 , as a risk factor for sALS, due to the eventual exposure to different toxic substances which are handled in farms working activities. So, a strong association was found between agricultural activity and sALS, while rural residence, by itself, did not influence the risk of the disease in one of those studies 18 . Differences in agricultural practices could explain the discrepancy between different findings done by different authors [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…So, a strong association was found between agricultural activity and sALS, while rural residence, by itself, did not influence the risk of the disease in one of those studies 18 . Differences in agricultural practices could explain the discrepancy between different findings done by different authors [16][17][18] . Occupation as a risk factor for sALS has been subjected to analysis in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another 46 relevant publications [3,9,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98] not fulfilling good scientific standards regarding the exposures under study are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%